Methanol steam reforming using In2O3/ZrO2coated catalytic static mixers (CSMs) - Kiermaier, Stephan; Nathrath, Phillip; Easton, Christopher D.; Greaves, Mark; Kohl, Thomas M.; Stöber, Robert; Hornung, Christian H.; Schühle, Patrick (Reaction Chemistry & Engineering, 2025)
Methanol is an attractive chemical hydrogen carrier that can provide hydrogen on demand by catalytic steam reforming – an endothermic reaction which requires efficient heat supply to the catalyst. The catalytic static mixer (CSM) technology offers an efficient way to provide sufficient heat and reactant supply to the catalytic center by high thermal conductivity and short diffusion pathways. In this study, an In2O3/ZrO2catalyst was deposited on highly conductive 3D printed stainless steel scaffolds, reaching uniform and durable coatings. These CSMs were investigated for the methanol steam reforming reaction in a single tube reactor at 330 °C and 350 °C. Their performance was compared to a conventional fixed bed configuration with In2O3/ZrO2pellet catalysts. The highest overall conversion for the methanol steam reforming, yielding 93%, was achieved using the CSM system at 330 °C, a low feed flow rate of 0.4 mL min−1and a water : MeOH ratio of 1 : 1. The highest CO2selectivity of 98% was achieved using the CSM system at 330 °C, a high feed flow rate of 2.0 mL min−1and a water : MeOH ratio of 1 : 2. For most experiments, the CSM results were slightly improved from the corresponding pellet results. Although this effect is believed to be small at the relatively small pipe diameter used herein, it is an indication of the expected superior heat transfer and fluid flow performance of the CSM system over pellets inside of a catalytic reactor.
CRIS-Team Scopus Importer:2025-12-05